Minimally Invasive Spine Osteosynthesis in Acute Dorso-Lumbar Trauma - Kandel, Prakriti Raj; Neupane, Kabin; Singh, Gyaneshwor Prasad (Nepal Orthopaedic Association Journal, 2019)
INTRODUCTION: The spine is a complex three-dimensional structure which provides protection of the spinal cord, load transmission, and the capacity for motion. The dorso-lumbar junction between the rigid thoracic vertebral column and the relatively mobile lumbar column creates a fulcrum at this junction, thus it remains the most common site of vertebral column injuries. The minimal invasive technique eliminates the need of large incision leading to shorter hospital stay and early recovery. METHOD: This prospective study was carried out at Department of Orthopedics of UCMS-TH between November 2015 to July 2017AD. Evaluations of the patients were done post-operatively according to modified Macnab criteria and by ASIA scoring. RESULTS: In our study the mean age was 39 years comprising 52% male and 48% female out of total 31 patients. Majority of fracture occurred in L 1 region ( 45 % ) where the common mechanism of injury (87%) was due to fall injury and most common fracture pattern was compression fracture (93%). The mean operative time was 155.77 minutes with average blood loss of 93.9 ml. 50% have excellent functional outcome according to Macnab’s criteria whereas 83.9% patient have ASIA score ’E’. Pain, implant failure and nerve root irritation were found in 39 %, 7 % and 3 % respectively. CONCLUSION: Minimal invasive spine osteosynthesis in acute dorso-lumbar trauma is one of the best treatments since it has small incision with minimum blood loss and good functional outcome. The procedure has minimal complication and helps in early mobilization of the patient with less damage to muscles and gives smaller scars.